The Role of Hope in Preventive Interventions. Issue 12 (December 2015) - Kwon, Paul; Birrueta, Maira; Faust, Emily; Brown, Emilia R.
Abstract: Preventive interventions have historically focused on reducing risk factors for psychological difficulties. Recent research has found that prevention programs are more effective when they enhance strengths, rather than merely reduce risk factors. An increased focus on strengths is consistent with a positive psychology perspective. In fact, hope has been found to be a central human strength in the positive psychology literature. Hope is associated with better adjustment, lower anxiety, lower depression, greater academic performance, and greater athletic achievement. In addition, individuals with high hope are able to respond more adaptively after traumatic events and physical illnesses. Intervention studies have shown that hope can be increased in individuals, and hope has been shown to predict more positive outcomes in psychotherapy. Future directions for research are outlined, including investigating hope as a preventive intervention for members of stigmatized groups, including ethnic minorities and lesbian, gay, and bisexual individuals.